MANAJEMEN MITIGASI BENCANA OLEH BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM MENANGGULANGI BENCANA KEKERINGAN DI KABUPATEN BOYOLALI - Fetria Septiarum; Maesaroh Maesaroh; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The highest drought disaster in Central Java Province was in Boyolali Regency. This study aims to analyze disaster mitigation management by the Regional Disaster Management Agency (BPBD) of Boyolali Regency in tackling drought disaster in Boyolali Regency and to find out the inhibiting factors of disaster mitigation management. The research method used is a qualitative research approach in analyzing predetermined research problems. The research subjects used purposive sampling and accidental sampling techniques, BPBD Boyolali Regency Field I Prevention and Preparedness and communities affected by drought. This study uses management functions by George R Terry which consist of planning, organizing, actuating, controlling. The results of the study show that there are still problems with the actuating phenomenon, namely in the implementation of activities jealousy arises between communities, the use of clean water is not good and programs/activities that are no longer running. The inhibiting factor is the absence of good supervision by BPBD Boyolali Regency in collecting clean water as evidenced by the absence of serial numbers and restrictions on the collection of clean water.